2014
DOI: 10.1002/tox.21996
|View full text |Cite
|
Sign up to set email alerts
|

Repeated dose and reproductive/developmental toxicity of perfluorododecanoic acid in rats

Abstract: Perfluoroalkyl carboxylic acids (PFCAs) are a series of environmental contaminants that have received attention because of their possible adverse effects on wildlife and human health. Although many toxicological studies have been performed on perfluorooctanoic acid with carbon chain length C8, available toxicity data on PFCAs with longer chains are still insufficient to evaluate their hazard. A combined repeated dose and reproductive/developmental toxicity screening study for perfluorododecanoic acid (PFDoA; C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 56 publications
0
41
1
Order By: Relevance
“…However, among studies, exact results have varied. These results are in stark contrast to studies in rodent models, which report significant declines in sperm counts upon exposure to PFASs (Fan et al 2005; Kato H et al 2015; Liu et al 2015). To date, no studies on occupationally exposed workers and semen parameters or pregnancy outcomes have been conducted, further contributing to the knowledge gap of whether PFASs impact male fertility.…”
Section: Introductioncontrasting
confidence: 96%
See 1 more Smart Citation
“…However, among studies, exact results have varied. These results are in stark contrast to studies in rodent models, which report significant declines in sperm counts upon exposure to PFASs (Fan et al 2005; Kato H et al 2015; Liu et al 2015). To date, no studies on occupationally exposed workers and semen parameters or pregnancy outcomes have been conducted, further contributing to the knowledge gap of whether PFASs impact male fertility.…”
Section: Introductioncontrasting
confidence: 96%
“…Most studies examining the impacts PFOS, PFOA, and PFNA on semen parameters do not report declines in semen volume or sperm number (Kvist et al 2012; Raymer et al 2012; Specht et al 2012; Toft et al 2012; Joensen et al 2013; Vested et al 2013; Governini et al 2015; Louis GM et al 2015). Studies in rodents assessing the impact PFASs have on spermatogenesis have shown significant declines in sperm count, in stark contrast to the results found in human studies (Fan et al 2005; Kato H et al 2015; Liu et al 2015) highlighting the disconnect between rodent and human studies. Rodent studies have identified Sertoli cells, seminiferous tubules, and the epididymis as targets of PFASs (Wan et al 2014; Zhang H et al 2014; Kato H et al 2015; Liu et al 2015; Lu et al 2016; Qiu et al 2016).…”
Section: Discussionmentioning
confidence: 87%
“…Perfluorododecanoic acid (PFDoA), which has chain lengths of 12 carbons, has been reported to be found in human serum (Goralczyk et al, 2015); thus, humans are exposed to PFDoA (Gebbink et al, 2015). The studies on the toxicity of PFCAs with carbon chain lengths longer than 10 are limited (Kato et al, 2015;Liu et al, 2016); therefore, it is necessary to estimate the toxicity of PFDoA. In general, PFCAs are thought to distribute predominantly to the blood, liver, and kidney, while having limited distribution to the brain in experimental animals (Kudo, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, induction of these genes was mild in spite of the high concentration of PFDoA in the liver. Kato et al (2015) have reported that hypertrophy, necrosis, and inflammatory cholestasis were observed in the liver after chronic administration of PFDoA at a dose of 0.5 and 2.5 mg/kg for 42-47 days in male rats. Hepatotoxicity of PFDoA has been shown to be due to production of reactive oxygen species in rats (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%